PsycEXTRA Dataset 2013
DOI: 10.1037/e633262013-541
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Shrinks Space

Abstract: Research investigating how people remember the distance of paths they walk has shown two apparently conflicting effects of experience during encoding on subsequent distance judgments. By the feature accumulation effect discrete path features such as turns, houses or other landmarks cause an increase in remembered distance. By the distractor effect performance of a concurrent task during path encoding causes a decrease in remembered distance. This study asks: What are the conditions that determine whether the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, some studies have found the opposite result. Liverence and Scholl (2012), for example, found that stimuli with more perceived segments were judged as shorter (see also Predebon, 1996;Sargent, Zacks, Philbeck, & Flores, 2013). Thus, it is still unclear how and when contextual changes exert their influence on prospective timing.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found the opposite result. Liverence and Scholl (2012), for example, found that stimuli with more perceived segments were judged as shorter (see also Predebon, 1996;Sargent, Zacks, Philbeck, & Flores, 2013). Thus, it is still unclear how and when contextual changes exert their influence on prospective timing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus cell phone use while walking leads to inattentional blindness for interesting objects near an individual’s path ( Hyman et al, 2010 ). Other forms of distraction and divided attention also lead to inattentional blindness ( Chabris et al, 2011 ) and to mistaken judgments of walking distance ( Sargent et al, 2013 ). In spite of lapses of awareness in these studies, people successfully navigated through complex environments.…”
Section: Introductionmentioning
confidence: 99%